Gaya Komunikasi Ustadzah Halimah Alaydrus di Media Sosial Studi pada Akun Instagram @halimahalaydrus - Fajriyah, Inayatul (Icon: Islamic Communication and Contemporary Media Studies, 2022)
In the context of da'wah through social media, especially Instagram, has become an effective means for preachers to reach a wider audience. One example of a preacher actively using social media is Ustadzah Halimah Alaydrus, who engages in da'wah actively through her personal Instagram account with the username @halimahalaydrus. The focus of this research is twofold: (1) to examine the communication style employed by Ustadzah Halimah Alaydrus on Instagram, (2) to investigate the audience's response to the da'wah videos posted by Ustadzah Halimah Alaydrus on Instagram. This research aims to understand the communication style used by Ustadzah Halimah Alaydrus on Instagram and explore the audience's responses to her da'wah videos. The study adopts a qualitative approach with a descriptive method, drawing on Kreitner & Knicki's theory that categorizes communication styles into Assertive, Aggressive, and Passive. The research employs virtual observation and documentation methods. Primary data is derived from two da'wah videos uploaded on the Instagram account @halimahalaydrus, while secondary data comes from literature such as books, journals, and online sources. The findings indicate that Ustadzah Halimah Alaydrus tends to use an assertive communication style. The audience's responses to her da'wah videos encompass cognitive, affective, and conative dimensions.